1996
DOI: 10.1063/1.116962
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoconductivity and Hall effects in La0.67Ca0.33MnO3

Abstract: The observed H2 and |H| dependence of the magnetoresistance above and below TC, respectively, may be explained by general time-reversal symmetry considerations. We further find empirically that the saturation observed in the magnetoresistance is best fit by a simple resistor in series with a magnetoconductor: ρ(H)=ρ∞+1/(σ0+γ|H|) for T<Tc and ρ(H)=ρ∞+1/(σ0+βH2) for T>TC. This provides a functional form to analyze and predict the magnetoresistance over a wide range of fields. This suggests that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
84
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 1 publication
12
84
0
Order By: Relevance
“…The low temperature limit of a 1 corresponds to a carrier density of ∼ 1.6 × 10 22 carriers per cm 3 (i.e., 0.9 holes per Mn site), larger than the nominal doping level (∼ 0.2 holes per Mn site). Similar deviations have been reported before and attributed to the inapplicability of the one-band model 14,15 . Figure 5 shows a 0 as a function of the zero-field ρ xx for films of different thicknesses.…”
Section: Resultssupporting
confidence: 72%
“…The low temperature limit of a 1 corresponds to a carrier density of ∼ 1.6 × 10 22 carriers per cm 3 (i.e., 0.9 holes per Mn site), larger than the nominal doping level (∼ 0.2 holes per Mn site). Similar deviations have been reported before and attributed to the inapplicability of the one-band model 14,15 . Figure 5 shows a 0 as a function of the zero-field ρ xx for films of different thicknesses.…”
Section: Resultssupporting
confidence: 72%
“…34 The hysteresis becomes apparent in the form of two split peaks near the coercive field, which are provided by the hysteretic behavior of the magnetization loop for the ferromagnet. 35 Therefore, it is concluded that the films with y Ն 0.65 at room temperature represent the magnetic phase-separated system, containing the FM and the paramagnetic ͑PM͒ clusters. As discussed previously, the formation of the multiphase magnetic state can also be affected by a nonuniform distribution of the lattice strain.…”
Section: Magnetic and Transport Propertiesmentioning
confidence: 99%
“…It is confirmed by the anhysteretic MR(H) behavior in a low-field range, which is contradicted with that for the similar films being in the completely FM state [32]. This hysteresis becomes apparent in the form of two splitted peaks located near a coercive field and is provided by the hysteretic behavior of magnetization loop for ferromagnet [33]. Therefore, one can conclude that our y ³ 0.65 films at room temperature represent the magnetic phase-separated system, containing the FM and paramagnetic (PM) clusters.…”
Section: Discussionmentioning
confidence: 52%